Stanje žagarske panoge v Sloveniji v letu 2019 - Ščap, Špela (Gozdarski vestnik, 2021)
The main objective of the survey was to assess the current situation in the sawmill industry in Slovenia (i.e., the number of sawmills, the amount of wood cut, the use of residues and the impact of the covid-19 pandemic). Prior to the 2019 survey, a list of 1,128 enterprises was compiled from various databases that registered C16 (wood processing) as their main or secondary activity. Completed questionnaires were provided by 588 companies, 328 of which are involved in the sawmilling activities. The total volume of the sawn roundwood recorded in 2019 was 1.71 million m3, with conifers predominating at 84%. The sawmills that participated in the survey produced 633,894 m3 of sawn timber products, 237,389 tons of sawdust and 252,655 m3 of bulky residues. In addition, 63% of participating companies were affected by the covid-19 epidemic during the first wave between March and May 2020.
Keywords: hardwood; iglavci; listavci; predelava; roundwood processing; sawmill industry; sawmill plants; sawn wood; softwood; žagan les; žagarski obrat; žagarstvo